(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical and radiographic features in patients with primary hip osteoarthritis according to ACR (1991) criteria and to analyze associations between clinical features and radiographic findings. Method: Cross-sectional descriptive study of 45 patients (51 hip joints) diagnosed with primary hip osteoarthritis per ACR (1991) criteria at Rheumatology Center of Bach Mai Hospital (July 2024 to August 2025). Results: Most common clinical features were: hip pain during walking (98.0%); functional limitation (60.8%); morning stiffness under 30 minutes (39.2%); pain with hip movement (84.3%); reduced range of flexion, internal rotation, and hip abduction (52.9%). Hip radiographic features: acetabular osteophytes (86.2%); femoral osteophytes (74.5%); subchondral sclerosis (76.5%); joint-space narrowing (58.8%); femoral head deformity (25.5%). The prevalence of Kellgren-Lawrence grades 3-4 was 58.8%. Patients with radiographic hip joint-space narrowing had higher odds of severe pain (VAS ≥ 5) than those without narrowing (OR = 12.8). Compared with Kellgren-Lawrence grades 1-2, those with Kellgren-Lawrence grades 3-4 had much higher odds of functional limitation and decreased range of motion 84 times and 130 times, respectively. Conclusion: Conventional hip X-ray has diagnostic value in determining and classifying the stage of hip osteoarthritis.